2004
DOI: 10.1002/ch.295
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and attitudes of Chinese regarding hypnosis and its applications

Abstract: The aim of the current study is to broadly consider the beliefs and attitudes of Hong Kong Chinese, regarding the notion of hypnosis and its applications. Particular attention is given to a comparison between the data of the current Chinese sample and those obtained by Western studies. Parameters such as self-perceived hypnotizability and psychology training are also examined. Four hundred and fifty-seven college students in Hong Kong were included in the study, and widely used inventories were adopted to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 11 publications
0
28
0
1
Order By: Relevance
“…There are only three studies regarding hypnosis that have been conducted in any Chinese-speaking country. Specifically, Yu (2004aYu ( , 2004bYu ( , 2005 has investigated hypnotizability with Cantonese-speaking samples in Hong Kong. The first two of these studies involved a self-report assessment of hypnotizability made without actually requiring the demonstration of hypnotic ability, while in the third study Yu incorporated the use of the Creative Imagination Scale (CIS; Barber & Wilson, 1978-1979.…”
mentioning
confidence: 99%
“…There are only three studies regarding hypnosis that have been conducted in any Chinese-speaking country. Specifically, Yu (2004aYu ( , 2004bYu ( , 2005 has investigated hypnotizability with Cantonese-speaking samples in Hong Kong. The first two of these studies involved a self-report assessment of hypnotizability made without actually requiring the demonstration of hypnotic ability, while in the third study Yu incorporated the use of the Creative Imagination Scale (CIS; Barber & Wilson, 1978-1979.…”
mentioning
confidence: 99%
“…Findings generated from the university student sample have been discussed in the first article (Yu, 2004). To reiterate, Chinese college students demonstrated precisely the same set of beliefs and 'misconceptions' that were reported in Western samples.…”
Section: Introductionmentioning
confidence: 91%
“…On the one hand, it is argued that the misunderstanding of hypnosis has an undesirable impact on people's attitudes (see Yu, 2004) and therefore their subsequent responses to the use of hypnosis for the purpose of research or therapy (McConkey and Jupp, 1986). On the other, Northcott (1996) highlighted the implication that the invalidated beliefs can foster a potentially very dangerous situation, which may result in the misapplication and abuse of hypnosis by the therapist.…”
Section: Research Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yu (2004) conducted an investigation using the OAH and the Attitudes Toward Hypnosis Questionnaire (ATHQ; Spanos, Brett, Menary, & Cross, 1987) in Hong Kong. The author reported that this investigation showed the same results as investigations in Western countries and that a number of people who had not experienced hypnosis previously regarded it as an "altered state of consciousness."…”
mentioning
confidence: 99%